2006
DOI: 10.1002/ldr.739
|View full text |Cite
|
Sign up to set email alerts
|

The relative efficiency of four representative cropland conversions in reducing water erosion: evidence from long‐term plots in the Loess hilly area, China

Abstract: Large areas of traditional slope cropland were recently converted to other land-use types in the semiarid Loess Plateau of China. In this study, we selected four representative conversion options of slope croplands, i.e., pastureland rotated with cropland (cultivated with Medicago sativa L. and rotated with Triticum aestivum L.), shrubland and woodland (afforested with Hippophae rhamnoides L. and Pinus tabulaeformis), and grassland (native herbage Stipa breviflora) to study the effect of landuse conversion by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Crop fields, with winter wheat accounting for 50-60% of the area, lose at least 5000 MgÁkm À2 Áyr À1 more soil to erosion than natural vegetation. This estimate is consistent with earlier reports that natural vegetation is able to decrease soil loss by 58-98% compared to cropland (Huang et al 2006, Wei et al 2007. A previous study by Kang et al (2001) revealed that plowed winter wheat fields had 2-3 times more soil erosion than corn and no-till cropfields between June and August.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Crop fields, with winter wheat accounting for 50-60% of the area, lose at least 5000 MgÁkm À2 Áyr À1 more soil to erosion than natural vegetation. This estimate is consistent with earlier reports that natural vegetation is able to decrease soil loss by 58-98% compared to cropland (Huang et al 2006, Wei et al 2007. A previous study by Kang et al (2001) revealed that plowed winter wheat fields had 2-3 times more soil erosion than corn and no-till cropfields between June and August.…”
Section: Resultssupporting
confidence: 92%
“…For example, was the erosion caused by poor cultivating practices or something innate about the particular crops grown? Other recent studies (Kang et al 2001, Huang et al 2006, Wei et al 2007) discussed the causes but did not assess the seasonal (monthly) relationship among vegetation, climate and soil erosion in depth. Such an assessment could enable a landscape-level understanding and ultimately facilitate the development of ecosystemmanagement and regional-planning strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, processes of carbon redistribution may also occur at the bottom of the valley in the STE site due to silt deposits and erosion by stream flow. According to the literature, runoff and erosion in forests are generally lower than in denuded and arable areas, and are similar to or greater than in pasture and shrub-land [9,15,40]. These processes are related to rainfall characteristics (volume, intensity, duration and Mean C 130 37 cm frequency), soil parameters, topography and vegetation structure.…”
Section: Impact Of Waterlogging On Carbon Stocksmentioning
confidence: 99%
“…Trees with large canopy are more effective in reducing wind speed, whereas shrubs are more effective in trapping transporting materials (Leenders et al, 2007). Compared to herbaceous species, shrubs have more developed root systems to improve soil structure and conserve water in deep layers, resulting in a better effect on soil and water conservation (Huang et al, 2006;Wei et al, 2009), and its effect is less affected by rain intensity compared to herbs (Zhang et al, 2014). Trees develop slowly (Ji et al, 2011) and have limited effect on soil protection during the early stage of development (Zhang and Shao, 2003), while herbs germinate and grow fast, rapidly covering the ground to prevent splash erosion and decrease runoff (Franklin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%